Behaviour of Escherichia coli O157:H7 in raw and mild pasteurised donkey milk treated with high pressure. (January 2023) - Dambrosio, Angela; Capuozzo, Flavia; De Palo, Pasquale; Mottola, Anna; Storelli, Maria M.; De Rosa, Michele; Matrella, Rosanna; Quaglia, Nicoletta C.
Abstract: The survival of Escherichia coli O157:H7 strain (NCTC 12900) was assessed in raw donkey milk, in mild pasteurised donkey milk (50 °C for 30 min), in donkey milk processed by HP at 400 MPa at 3 °C for 60 s, and in donkey milk treated with a combination of the two technologies. The results showed that E. coli O157:H7 was able to survive in raw donkey milk for 15 days and in mild pasteurised donkey milk for 4 days. Treatment of raw milk and pasteurised milk with HP, ensured the death of the pathogen, since it was not detected from day 0. Therefore, the use of HPP proved to be effective in providing the microbiological safety of the product. Further studies are needed to evaluate the effects of mild technological treatments on the antibacterial and nutritional components of donkey milk to guarantee a safe and nutritionally good product.